Transcriptomic Analysis of Liver Indicates Novel Vaccine to Porcine Reproductive and Respiratory Virus Promotes Homeostasis in T-Cell and Inflammatory Immune Responses Compared to a Commercial Vaccine in Pigs - Fleming, Damarius S.; Miller, Laura C.; Li, Jiuyi; Van Geelen, Albert; Sang, Yongming (Frontiers in Veterinary Science, 2022)
One of the largest impediments for commercial swine production is the presence of Porcine Reproductive and Respiratory Syndrome virus (PRRSV), a devastating RNA viral infection that is responsible for over $1 billion in loss in the U.S. annually. The challenge with combating PRRSV is a combination of the effect of an extraordinary rate of mutation, the ability to infect macrophages, and subversion of host immune response through a series of actions leading to both immunomodulation and immune evasion. Currently there are a handful of commercial vaccines on the market that have been shown to be effective against homologous infections, but struggle against heterologous or mixed strain infections. However, vaccination is the current best strategy for combating PRRSV, making research into new vaccine technology key. To address these issues with PRRSV and host antiviral functions a novel modified-live vaccine (MLV) able to stimulate known anti-viral interferons was created and examined for its ability to potentiate effective immunity and better protection. Here, we examine gene expression in the liver of pigs vaccinated with our novel vaccine, given the liver’s large role in anti-viral responses and vaccine metabolism. Our study indicated that pigs administered the novel vaccine experience homeostatic gene expression consistent with less inflammation and T-cell depletion risk than pigs administered the commercial vaccine.